Pathogenicity of Salmonella Enteritidis Phage Type 1 (Malaysian isolate) in Specific Pathogen-Free Chickens. - Faraj, Ahmad Sadik (2010)
Salmonella enteritidis (SE) is one of the major concerns to poultry industry thoughout years. SE causes food poisoning due to consumption of poultry or poultry products contaminated by the bacteria. Many SE phage types have been prevailed around the world especially phage types 4, 8, 13a and 23 and few others with less isolation rates. The SE phage type 1 has increased in incidence to become one of the major phage types isolated from Europe, Asia and few other countries. It was the objective of this study to isolate and characterize the phage type of SE isolated from commercial poultry farm in Malaysia and to determine its pathogenicity in one-day-old and 21-day-old specificpathogen-free (SPF) chickens, upon oral inoculation. White Leghorn SPF one-day-old and 21-day-old chicks were divided into three groups namely the SE, Control and Mortality groups. The chicks in the SE and Mortality groups were inoculated orally with SE phage type (PT) 1 at a concentration of 1x10 8 cfu/mL. The clicks in SE and Control groups were sacrificed at 6 and 12 hrs post inoculation (pi) and at 1, 2, 3, 5, 7, 10, 14 and 21 days pi. The chicks were observed for the clinical signs, body weight gain and gross lesions. Tissue samples were collected for bacteriological isolation, histopathological and ultrastructural analysis. The study in one-day-old chicks showed weight loss in the SE group starting from day 2 pi and until the end of the trial reaching its peak at day 21 pi when the SE group weight was 39% less compared to the Control group. Diarrhea, pasty vents, inappetance and stunted chicks were recorded starting at 12 hrs pi and until the end of the trial throughout the trial. No mortality was recorded in the Mortality group. However two chicks from the SE group died at days 3 and 5 pi. Grossly the chicks exhibited mild air sacculitis, peritonitis and mild congestion of the liver and kidney starting at day 2 pi until the end of the trial. No abnormal gross changes or clinical sign were recorded in the Control group throughout the trial. The bacteria were isolated in the SE group as early as 6 hrs pi from all organs which include the liver, spleen and cloacal swabs (66%), caecum and caecal tonsils (100%) and small intestine content and blood (33%). At day 14 pi, SE was isolated only from the liver, spleen and caecal tonsils (33%). Histopathological observed were enteritis in the duodenum, jejunum, ileum and caecum and necrosis of the enterocytes at the apical part of the intestinal villi with the presence of necrotic debris and bacterial clusters in the lumen starting at 12 hr pi until the end of the trial. Hepatitis with coagulative necrotic foci was recorded starting at 3 days pi until the end of the trial. The splenic tissue showed an increased heterophilic infiltration and mild congestion with few focal necrotic areas at 2 days pi until the end of the trial. While in the bursa of Fabricius congestion, heterophilic infiltration and necrosis of the lymphoid follicles were recorded starting day 5 pi until the end of the trial. The villi height showed a significant (p<0.05) decreased in the SE group when compared to the Control group starting day 1 pi until the end of the trial in the duodenum and jejunum, while in the ileum it started at 6 hrs pi until the end of the trial. However, crypts depth measurement remained unchanged throughout the trial. The bacterial engulfment by macrophages and penetration to the villi wall though areas of necrotized microvilli surface was recorded starting 6 hrs pi and until the end of the trial under SEM in the SE group. The study in 21-day-old chickens showed no mortality in all groups. However the body weight was constantly reduced in the SE group starting at day 7 pi until the end of the trial, reaching a peak at day 14 pi when the body weight in SE group measured 26% lower than the Control group. Diarrhea was recorded in the SE group starting from day 2 pi until day 7 pi. Grossly mild air sacculitis, peritonitis and mild congestion of liver were obsedved from day 2 pi to day 5 pi. The bacteria was first isolated from the caecum (66%) at 12 hrs pi and remained positive until day 3 pi (33%) where they were was also isolated from the liver (33%), blood (33%), spleen (33%) and small intestine content (33%). In addition, SE were also isolated from the spleen (33%) and caecal tonsils (66%) at days 1 and 2 pi, respectively. In contrast, SE were not isolated from the cloacal swabs throughout the trial. Histological examination revealed hepatitis with coagulative necrotic foci in the liver at day 2 pi and until the end of the trial. Enteritis with necrosis and sloughing of the enterocytes in the apical part of the duodenum, jejunum, ileum and caecal villi was observed starting at day 1 pi and until the end of the trial. Increased heterophilic infiltration and congestion were observed in the spleen at day 1 pi and until the end of the trial. Congestion, heterophilic infiltration and areas of focal coagulative necrosis in the lymphoid follicles were observed in the bursa of Fabricius starting at day 3 pi until the end of the trial. The instestinal villi in the duodenum in the SE group was lower than those of the Control group throughout the trial, while in the jejunum it was lower in the SE group starting at day 2 pi until the end of the trial, and in the ileum starting at day 14 pi and until the end of the trial. Intestinal crypts depth remained unchanged in the SE group when compared to the Control group. The bacteria were seen to be engulfed by the macrophages in the caecal tonsils and also making their way into the enterocytes at the villi surface through the necrotized and sloughed areas of the microvilli starting at day 1 pi and until the end of the trial. It was concluded that the pathogenicity of SE PT 1 isolate of Malaysia is a mild to moderate one-day-old and mild in and 21-day-old SPF chickens. The SE isolate was able to cause systemic infection, body weight loss and possibly transmitting the infection from chicken to chicken.